2023
DOI: 10.3389/fendo.2023.1119658
|View full text |Cite
|
Sign up to set email alerts
|

Sex- and age-specific association between outdoor light at night and obesity in Chinese adults: A national cross-sectional study of 98,658 participants from 162 study sites

Abstract: BackgroundExposure to light at night (LAN) is a potent disruptor of the circadian system. Whether LAN exposure exerts a sex- or age-specific influence on obesity needs investigation.ObjectivesTo estimate the sex- and age-specific associations of exposure to outdoor LAN and obesity based on a national and cross-sectional survey.MethodsThe study included a nationally representative sample of 98,658 adults aged ≥ 18 years who had lived in their current residence for ≥ 6 months from 162 study sites across mainland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Additionally, inflammation may provide another possible explanation. Studies have demonstrated that autoimmune factors are common etiological factors in hypothyroidism 40,41 . Alterations in the immune system can lead to chronic inflammation of the thyroid tissue 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, inflammation may provide another possible explanation. Studies have demonstrated that autoimmune factors are common etiological factors in hypothyroidism 40,41 . Alterations in the immune system can lead to chronic inflammation of the thyroid tissue 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Overall, daylight is beneficial and strengthens the alignment power of light signaling [4,9,63], whereas light at night is linked to circadian misalignment and is detrimental to health [64][65][66]. Light at night is linked to adverse metabolic changes and weight gain in laboratory animals [67][68][69] and humans [60,[70][71][72][73][74].…”
Section: Discussionmentioning
confidence: 99%